The Importance Of The Compromise Model “School Of Example” In Strengthening Family Relationships - Tashmuradov Mirolim Ismoil ugli (Zien Journals, 2025)
This article analyzes the “Exemplary School” compromise model as a moral and philosophical factor in strengthening family relationships. The study reveals the role of the principle of compromise in the formation of mutual respect, tolerance, and responsibility among family members. The “Exemplary School” model is highlighted as an educational system that serves to ensure family stability based on human qualities, values, and moral examples. The article substantiates the socio-psychological mechanisms of mutual compromise, the constructive resolution of family conflicts, and the pedagogical significance of example in raising children. As a result, the model of compromise “School of Example” is interpreted as a conceptual approach that ensures spiritual stability in strengthening the modern institution of the family
Keywords: School of Example; compromise; family; moral values